Documentation of The Saperra Manre Through The Documentary Film - Suparman; Sehe Madeamin; Pancana Beta (Penerbit STKIP PGRI Bangkalan, 2018)
This study aims to document the value of manre saperra in terms of preserving andrestoring noble values in regional culture as well as strengthening the character of thenation's children in facing globalization. Research method that is qualitative methodthat used as base of thought to solve problem which sourced from literature andinformation from informant. Quantitative methods are used to determine the selectedalternatives based on qualitative dataThis research will be conducted in Luwu UtaraDistrict. The data source of this research is the ritual procession of manre saperra ofNorth Luwu society. This documentary was made with the stages of data collection inthe form of research observation, interview, literature study, and film compilation. Theresult of this research is by making a documentary about manre saperra procession, thesociety is expected to be more know and recognize and practice the values contained inmanre saperra ritual so that this documentary film can be used as media of informationand learning media for younger genres in knowing local culture.